Mechanisms and salvage treatments in patients with multiple myeloma relapsed post-BCMA CAR-T cell therapy - Fu, Bingjie; Liu, Rui; Gao, Gongzhizi; Lin, Zujie; He, Aili (Frontiers in Immunology, 2024)
Chimeric antigen receptor T-cell (CAR-T) therapy has ushered in a new era for the treatment of multiple myeloma (MM). Numerous clinical studies, especially those involving B-cell maturation antigen (BCMA)-directed CAR-T, have shown remarkable efficacy in patients with relapsed or refractory multiple myeloma (R/R MM). However, a considerable number of patients still experience disease recurrence or progression after BCMA CAR-T treatment, which is attributed to various factors, including antigen escape, CAR-T manufacturing factors, T cell exhaustion, inhibitory effects of tumor microenvironment and impact of prior treatments. The scarcity of effective treatment options following post-CAR-T disease recurrence, coupled with the lack of well-established salvage regimens, leaves patients who do relapse facing a bleak prognosis. In recent years, some academic institutions have achieved certain results in salvage treatments of patients with relapse after BCMA CAR-T treatment through secondary infusion of BCMA CAR-T, changing to non-BCMA-directed CAR-T, double-target CAR-T, bispecific antibodies or other novel therapies. This review summarizes the mechanisms of resistance or relapse after BCMA CAR-T administration and the available data on current salvage treatments, hoping to provide ideas for optimizing clinical salvage therapies.